PEMBINAAN PENULISAN KARYA ILMIAH DAN LITERASI PENCEGAHAN PLAGIARISME DI SMK PERTIWI BATAM - Tomi Arianto; Ambalegin Ambalegin; Padrisan Jamba (PUAN INDONESIA, 2021)
Writing scientific papers is inseparable from the life of academic source. Scientific writing is not only an obligation and an interest at the college level but also at the school level. The problem that exists when the team did an observation at school, the lack of an atmosphere of writing scientific papers for both teachers and students made the level production of scientific papers in schools very low. Students were preoccupied with theoretical learning and the target of pursuing the test scores as well as the teacher was spent time fulfilling all the learning outcomes in class. Important things that could be used by teachers and students to excel in the field of scientific writing are eliminated. On the other hand, awareness and understanding of plagiarism problems such as the method of citing or writing references was still low. Those were also driven by a lack of writing atmosphere at the school level and a lack of understanding of plagiarism itself. With the various obstacles and phenomena found, the school's target community service team collaborated with multi-disciplinary lecturers by involving students to find solutions to these problems. This activity was carried out at SMK Pertiwi Batam by involving students and teachers. The results of this dedication showed the high enthusiasm of teachers and students as well as the ability to write scientific papers and awareness to prevent plagiarism. This services was held for 6 meetings from January to April 2021. This activity was attended by 30 participants who were held online with media zoom. Each meeting is held for 1.5 hours. The implementation of these services began with the provision of knowledge about scientific papers, methods, techniques, and materials related to classroom action research. Service is also given the legal approach regarding plagiarism.